Valorisation of sugarcane bagasse ash (SCBA) with high quartz content as pozzolanic material in Portland cement mixtures - Pereira, A. M. [UNESP]; Moraes, J. C.B. [UNESP]; Moraes, M. J.B. [UNESP]; Akasaki, J. L. [UNESP]; Tashima, M. M. [UNESP]; Soriano, L.; Monzó, J.; Payá, J. (Editorial CSIC, 2018)
Portland cement (OPC) production is one of the most contaminating greenhouse gas producing activities. In order to reduce OPC consumption, several alternatives are being assessed, and the use of pozzolanic material is one of them. This paper presents study on the reactivity of sugarcane bagasse ash (SCBA), a residue from sugarcane industry, as a pozzolanic material. In order to evaluate SCBA reactivity, it was mixed in pastes with hydrated lime and OPC, which were microstructurally characterised. These studies showed that SCBA presents some pozzolanic characteristics. Studies on mortars in which OPC was replaced by SCBA in the range 10-30% were also carried out. Replacement in the range 15-20% yielded the best behaviour in terms of compressive strength. Finally, it can be concluded this ash could be valorised despite its relative low pozzolanic reactivity.
Keywords: Active addition; Compressive strength; Mortar; Pozzolane; Thermal analysis